Backside wear, particle migration and effectiveness of screw hole plugs in acetabular hip joint replacement with cross-linked polyethylene - Braun, Steffen; Müller, Ulrike; Schröder, Stefan; Sonntag, Robert; Bormann, Therese; Kretzer, Jan Philippe (Acta biomaterialia, 2019)
In total hip arthroplasty, osteolysis of the acetabulum often occurs at the backside of cups in the area of screw holes, indicating a clinically relevant amount of polyethylene (PE) wear particles in this area. In order to avoid a possible migration of wear particles to the acetabulum-bone, screw hole plugs are provided for some implant systems. The aims of this study were to quantitatively determine backside wear and to investigate the migration behaviour of articulation-related wear particles in a cup system with open and closed screw holes by plugs. Titanium cup systems with backside holes for screw fixations were sinusoidally loaded with 2.7kN. The articulation area was separated from the backside area of the cup. A defined amount of articulation-generated particles was added to the fluid of the articulation chamber. The fluids in the two chambers were separately filtered after 2×106 cycles for a particle analysis. Backside wear with noticeably small (65.6±4.2nm) and round PE particles was identified. With both open and closed screw holes, a migration of the articulating wear particles from the articulation area behind the cup could be observed. Backside wear was estimated to be below 1% of the articulated wear. Screw hole plugs did not effectively prevent the migration of PE wear particles behind the investigated cups. - Statement of Significance - Backside wear occurs in a proven cup-system. Furthermore, it was quantitatively observed that articulation-generated wear products could migrate from the articulating area along the cup/liner-interface through the screw holes behind the cup. An almost unimpeded particle migration to the acetabulum-bone, in conjunction with very small backside wear particles, could produce a clinically relevant amount of PE with respect to pelvic lysis. These findings highlight the importance of management to avoid particle migration in artificial hip cups. Therefore, primarily the use of screw hole plugs, as far as available for the respective cup-system, is recommended. The aim of avoiding particle migration by plugs, but also by using a sophisticated anchoring mechanism between cup and PE liner should continue in future.
Gesehen am 16.03.2020